Campylobacters and their bacteriophages from chicken liver: the prospect for phage biocontrol - Firlieyanti, Antung S.; Connerton, Phillippa L.; Connerton, Ian F. (Elsevier, 2016)
Consumption of foods containing chicken liver has been associated with Campylobacter enteritis. Campylobacters can contaminate the surface of livers post-mortem but can also arise through systemic infection of colonising bacteria in live birds. The use of bacteriophage to reduce levels of Campylobacter entering the food chain is a promising intervention approach but most phages have been isolated from chicken excreta. This study examined the incidence and contamination levels of Campylobacter and their bacteriophage in UK retail chicken liver. Using enrichment procedures, 87% of 109 chicken livers were surface contaminated with Campylobacter and 83% contaminated within internal tissues. Direct plating on selective agar allowed enumeration of viable bacteria from 43 % of liver samples with counts ranging from 1.8 - > 3.8 log10 CFU/cm2 for surface samples, and 3.0 – > 3.8 log10 CFU/g for internal tissue samples. Three C. jejuni isolates recovered from internal liver tissues were assessed for their ability to colonise the intestines and extra-intestinal organs of broiler chickens following oral infection. All isolates efficiently colonised the chicken intestines but were variable in their abilities to colonise extra-intestinal organs. One isolate, CLB104, could be recovered by enrichment from the livers and kidneys of three of seven chickens. Campylobacter isolates remained viable within fresh livers stored at 4oC over 72 h and frozen livers stored at -20oC over 7 d in atmospheric oxygen, and therefore constitute a risk to human health. Only three Campylobacter-specific bacteriophages were isolated, and these exhibited a limited host range against the Camplylobacter chicken liver isolates. All were identified as group III virulent bacteriophage based on their genome size of 140 kb. The application of broad host range group II virulent phages (8 log10 PFU/g) to liver homogenates containing C. jejuni strains of diverse origin at 4oC resulted in modest but significant reductions in the viable counts ranging from 0.2 to 0.7 log10 CFU/g.